Urgency Surgery of Superior Mesenteric Artery - Matteucci, Pablo; Lucinschi, Alicia (Cirugía del Uruguay, 1980)
Urgency surgery of superior mesenteric artery should only be performed when it is the sale chance of recovery in cases of massive intestinal infarction a:nd ·in_ patients with a reasonable chance of survivaJ. Description of procedure is accompanied by státistics from the Hospital de Clínicas (University Medical School Hospital) of Montevideo, where, in the Iast six years out of 38 cases of intestinal' infarction, revascularization of superior mesenteric artery was performed 7 times, with 2 survivals.